Toll-like receptor 9 agonists promote cellular invasion by increasing matrix metalloproteinase activity - Merrell, Melinda A; Ilvesaro, Joanna M; Lehtonen, Niko; Sorsa, Timo; Gehrs, Bradley; Rosenthal, Eben; Chen, Dongquan; Shackley, Brit; Harris, Kevin W; Selander, Katri S (Molecular cancer research, 2006)
Toll-like receptor 9 (TLR9) recognizes microbial DNA. We show here that TLR9 protein is expressed in human breast cancer cells and clinical breast cancer samples. Stimulation of TLR9-expressing breast cancer cells with the TLR9 agonistic CpG oligonucleotides (1-10 mumol/L) dramatically increased their in vitro invasion in both Matrigel assays and three-dimensional collagen cultures. Similar effects on invasion were seen in TLR9-expressing astrocytoma and glioblastoma cells and in the immortalized human breast epithelial cell line MCF-10A. This effect was not, however, dependent on the CpG content of the TLR9 ligands because the non-CpG oligonucleotides induced invasion of TLR9-expressing cells. CpG or non-CpG oligonucleotide-induced invasion in MDA-MB-231 cells was blunted by chloroquine and they did not induce invasion of TLR9(-) breast cancer cells. Treatment of MDA-MB-231 cells with CpG or non-CpG oligonucleotides induced the formation of approximately 50-kDa gelatinolytic band in zymograms. This band and the increased invasion were abolished by a matrix metalloproteinase (MMP) inhibitor GM6001 but not by a serine proteinase inhibitor aprotinin. Furthermore, CpG oligonucleotide treatment decreased tissue inhibitor of metalloproteinase-3 expression and increased levels of active MMP-13 in TLR9-expressing but not TLR9(-) breast cancer cells without affecting MMP-8. Neutralizing anti-MMP-13 antibodies inhibited the CpG oligonucleotide-induced invasion. These findings suggest that infections may promote cancer progression through a novel TLR9-mediated mechanism. They also propose a new molecular target for cancer therapy, because TLR9 has not been associated with cancer invasiveness previously.